2020
DOI: 10.1016/j.eap.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Inequality and gender economic inclusion: The moderating role of financial access in Sub-Saharan Africa

Abstract: This study assesses how financial access can be used to modulate the effect of income inequality on gender economic inclusion. The focus is on 42 countries in sub-Saharan Africa (SSA) for the period 2004-2014 and the empirical evidence is based on Generalised Method of Moments (GMM) and Fixed Effects (FE) regressions. Significant results are not apparent in the FE regressions. The following main findings are established from the GMM estimations. There is a negative net effect from the role of financial access … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 113 publications
1
47
0
Order By: Relevance
“…Consistent with contemporary literature (Tchamyou, Erreygers & Cassimon, 2019;Asongu, Nnanna & Acha-Anyi, 2020a, 2020b, there are two main theories linking finance to inclusive development, notably: the intensive margin theory and the extensive margin theory.…”
Section: Introductionmentioning
confidence: 57%
“…Consistent with contemporary literature (Tchamyou, Erreygers & Cassimon, 2019;Asongu, Nnanna & Acha-Anyi, 2020a, 2020b, there are two main theories linking finance to inclusive development, notably: the intensive margin theory and the extensive margin theory.…”
Section: Introductionmentioning
confidence: 57%
“…The above theoretical contribution should be understood in the light of the fact that the intensive margin theory broadly focuses on improving financial access and services to existing holders of bank accounts and users of bank services (which mostly consists of the rich fraction of the population) while the extensive margin theory is understood as an extension of the attendant bank services to poorer elements of society who do not have formal bank accounts (Evans & Jovanovic, 1989;Holtz-Eakin, Joulfaian & Rosen, 1994;Black & Lynch, 1996;Bae, Han & Sohn, 2012;Chipote, Mgxekwa & Godza, 2014;Odhiambo, 2014;Orji, Aguegboh & Anthony-Orji, 2015;Batabyal & Chowdhury, 2015;Chiwira, Bakwena, Mupimpila & Tlhalefang, 2016). Moreover, consistent with contemporary literature, both theoretical insights can be taken on board in an empirical exercise within the framework of interactive regressions (Tchamyou et al, 2019a;Asongu, Nnanna & Acha-Anyi, 2020).…”
Section: Nexus With the Literature And Contributions To Practice And Theorymentioning
confidence: 84%
“…However, productive SMEs in the formal sector in African countries have been hampered by numerous non-financial constraints, including low revenue collection and the lack of social protection, as highlighted in Auriol (2014) or by the lack of skills (Brixiová, 2010). 4 SME financing has attracted considerable attention from policymakers, researchers and development partners (Stein et al, 2010;Beck and Demirguc-Kunt, 2006;Jacob, 2017;Fowowe, 2017;Quartey et al, 2017;Dao and Liu, 2017;Asongu and Odhiambo, 2018;Asongu et al, 2020). Within the literature on the constraints to productive entrepreneurship, this paper builds on the stream emphasizing the limited access to credit due to either functioning of commercial banks, institutional imperfections or entrepreneurs themselves.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…Policymakers and researchers have recognized that financial inclusion is a key dimension as well as a strong driver of inclusive growth. Access to financial services could also boost employability and women labor participation by providing them with the means to invest in education and training (Asongu and Odhiambo, 2018;Asongu et al, 2020). Beck et al (2005) showed that relaxing financial constraints positively impacts SMEs' employment growth.…”
Section: Introductionmentioning
confidence: 99%